REVIEW: OPTIMALISASI METODE MASERASI UNTUK EKSTRAKSI TANIN RENDEMEN TINGGI - Fakhruzy, Fakhruzy (LPPM Universitas Muhammadiyah Sumatera Barat, 2020)
Tannin is a compound from the results of secondary plant metabolites. The use of tannins in the field of research is increasingly interesting to be developed. The effect of tannin extraction method is very influential on the levels of tannin produced. The method often used is the maceration method, this is because this method is simpler and easier. Factors that determine the high yield of tannins produced after maceration extraction are temperature, time, and type of solvent used. The longer the temperature and time also do not determine the high yield produced, on the contrary the resulting tannin levels will be low. Low solvent concentration also will not produce high tannin yield Keywords: tannin, temperature, time, solvent concentration